(untitled) (Citizenship in Action: Extension and Culture Magazine, 2020)
This article is the result of listening at the beginning of the 2019 of the school year with students from Young and Adult Education - EJA, High School, from the Polivalente College of Caravelas. In order to make the mathematics developed in this type of education more attractive and dynamic, this paper aims to show the use of printed material and games, as didactic-pedagogical possibilities for the construction of mathematical knowledge. Many students in this class have developed repulsive reactions in relation to this field of knowledge. In this interaction, it was found that the way that this area of knowledge was presented to these students contributed negatively, making it uninteresting. For this reason, it was decided to develop a teaching and learning practice based on elements that stimulate, enable and favor the relationship of these students with mathematical concepts and ideas. For that, it relies so much on Freire (1996), who defends an education based on the principle of dialogicity, on listening practice, on wanting the student well, and on Muniz (2001), who proposes a mathematical education based on situations linked to games, the use of printed materials, among others, as contexts favorable to mathematical knowledge. In this reasoning, guidelines that reflect EJA in Bahia were also emphasized. The results of the applied activities prove that when we learn like this, through the game and the use of printed material, mathematical contents have great chances of being incorporated more naturally and easily, which in a way favors their understanding, their understanding.